Prenatal Smoking Cessation Intervention and Gestational Weight Gain - Levine, Michele D. (2013)
BACKGROUND: Quitting smoking is often associated with weight gain and prenatal cessation may lead to increased gestational weight gain (GWG). Although previous reports have suggested a link between prenatal smoking cessation and GWG, no studies have examined the relationship between cessation and guideline-recommended GWG, and there is little information about the relationship between the timing of prenatal cessation and GWG. Thus, we examine GWG among women in a community prenatal smoking cessation program and assess the relationship between the timing of prenatal cessation GWG. METHODS: Pregnant women health care clinics serving economically disadvantaged women who participated in a smoking cessation intervention offered free of charge, self-reported weight, and provided biochemical verification of smoking. Relationships between duration of cessation and GWG were evaluated in t-tests and regression models. GWG was calculated from self-reported weight before pregnancy and self-reported weight at the last visit before delivery. FINDINGS: Women who quit earlier during pregnancy had greater GWG (16.9 ± 7.5 kg) than did those who never quit (13.6 ± 8.9). After adjusting for timing of weight assessment and prepregnancy body mass index, however, GWG was not different between women who did and did not quit. CONCLUSION: Quitting earlier in pregnancy is associated with greater GWG, but women who do and do not quit do not differ on total GWG. Despite increased GWG with early cessation, the maternal and fetal health benefits of prenatal smoking cessation outweigh risks of potential risks of excessive GWG.